2018
DOI: 10.1016/j.jid.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Relief of Acute and Chronic Itch Requires TRPM8 Channels and Neurons

Abstract: Cooling or the application of mentholated liniments to the skin has been used to treat itch for centuries, yet remarkably little is known about how counter-stimuli such as these induce itch relief. Indeed, there is no clear consensus in the scientific literature as to whether or not cooling does in fact block the transduction of itch signals or if it is simply a placebo effect. This gap in our understanding led us to hypothesize that cooling is antipruritic and, like cooling analgesia, requires function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 46 publications
(84 reference statements)
0
54
0
Order By: Relevance
“…Indeed, it has been shown that TRPM8-expressing DRG neurons are required for inhibition of itch by cooling and furthermore, that topical application of menthol inhibits chloroquine-evoked itch behaviors (Palkar et al, 2018). Thus, targeting TTX-sensitive Na V 1.1 channels in mentholsensitive DRG neurons might prove to be a new direction for the treatment of various sensory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that TRPM8-expressing DRG neurons are required for inhibition of itch by cooling and furthermore, that topical application of menthol inhibits chloroquine-evoked itch behaviors (Palkar et al, 2018). Thus, targeting TTX-sensitive Na V 1.1 channels in mentholsensitive DRG neurons might prove to be a new direction for the treatment of various sensory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stimuli, pain (conveyed by TRPV1 and TRPA1 positive nerves), and cooling (transduced through transient receptor potential melastatin [TRPM] 8 positive nerves) can attenuate itch sensation. [49][50][51] These sensations activate helixloop-helix family member B5 (Bhlhb5)-positive inhibitory interneurons. These interneurons exert their inhibitory effect on GPRP-positive neurons through releasing inhibitory neurotransmitters: dynorphin, glycine, and gamma-amino butyric acid.…”
Section: Itch Processing In the Spinal Cordmentioning
confidence: 99%
“…TRP cation channel subfamily M member 8 (TRPM8) channels are located on the end of epidermal nerve fibres and Merkel cells (107). TRPM8 channels are cold-gated ion channels that inhibit both the histaminergic and non-histaminergic itch sensory pathways when activated (108). A novel TRPM8 cooling compound has been developed that, when incorporated into a lotion, signi- Defective corneocyte envelope formation (91), and defective lipid content and metabolism (92) Increased transepidermal water loss and abnormal permeability (93) Psoriasis Abnormal epidermal differentiation and immunological deviations, e.g.…”
Section: Novel Targets For Topical Treatments and Ingredientsmentioning
confidence: 99%